The real UVB photoprotective efficacy of vegetable oils: in vitro and in vivo studies - Ácsová, Aneta; Hojerová, Jarmila; Janotková, Lívia; Bendová, Hana; Jedličková, Lucie; Hamranová, Veronika; Martiniaková, Silvia (Photochemical & photobiological sciences, 2021)
Some vegetable oils are currently being promoted as a safe alternative to commercial sunscreens. The true UVB photoprotective efficacy of 14 virgin vegetable oils and the suitability of the dilution method for determining their SPF value were evaluated. Oils and standard sunscreens were investigated in vitro by the Mansur's method in Slovakia and in vivo by the ISO method in the Czech Republic. SPF values in vitro (0.1; 0.0; 0.4; 0.2 and 0.2) and in vivo (2.5; 1.2; 2.6; 2.6; and 2.8) of the five most promoted oils (from carrot seed, coconut, raspberry seed, rosehip seed, and wheat germ) were significantly lower than the values reported in the controversial studies. We have shown that the overestimated SPF values of these oils were determined by authors who did not strictly follow Mansur's original methodology. The other eight vegetable oils also provide no or negligible SPF values. Only the in vitro SPF value of 11.2 tamanu oil is worth mentioning, probably due to high proportion of calophyllolides. In vitro and in vivo SPF ratios from 1.14 to 0.94 obtained by two methods in two laboratories for six commercial sunscreen oils used as controls confirm the correctness of performing the Mansur's method in this study. However, this dilution method has proven to be fundamentally flawed in determining the SPF value of substances with such negligible photoprotection as most vegetable oils can provide. An SPF value of less than 1, which can be determined by this Mansur's method, is physiologically impossible and meaningless.
Keywords: dospělí; Benzimidazoles; Female; Mansur's method; přípravky chránící proti slunci; False SPF values; Adult; Seeds; ženské pohlaví; Sunscreening Agents; semena rostlinná; benzimidazoly; lidé; Plant Oils; Ultraviolet Rays; Sun Protection Factor; kůže; Rubus; Aged; Skin; Vegetable oil; oleje rostlin; lidé středního věku; Sunscreen; senioři; ochranný sluneční faktor; Middle Aged; ultrafialové záření; Humans